Consumption and export potential of tea in Bangladesh: A field study - Shefali Boonerjee; M. Ashraful Islam; S.M. Monwarul Islam; Shovon Kumar Paul; M.T. Uddin; M.S. Alamgir (Journal of Agriculture and Food Research)
Tea is one of the most popular beverages globally and holds a significant position in Bangladesh. Tea is deeply embedded in Bangladeshi culture as a low-cost, social beverage. The tea industry in Bangladesh is a vital sector, providing substantial employment opportunities and contributing significantly to the national economy. Socio-economic advancements have further heightened the prevalence of tea consumption, leading to a notable increase in domestic demand. This investigation aimed to document the actual tea consumption rate and explore potential avenues for export. Our study indicated that current production levels are sufficient to meet domestic demand, although export volumes remain minimal. The investigation utilized field visits, interviews, and online surveys across multiple regions of Bangladesh to estimate daily tea consumption and annual demand. The result revealed that approximately 92.15 million kilograms of tea are consumed annually, equating to 142.8 million cups per day. The per capita yearly tea consumption was calculated to be 550 g. In 2021 and 2022, domestic consumption accounted for 95.48 % and 98.21 % of the total production of 96.51 million kilograms and 93.829 million kilograms, respectively. This left a surplus of 1.95 million kilograms in 2022. Projection analysis suggests positive growth trends in exports (R2 = 0.867), production (R2 = 0.7557), and consumption (R2 = 0.9369), highlighting opportunities to expand both domestic and international markets. The findings provide a strong foundation for policymakers and stakeholders to optimize the role of Bangladesh's tea industry in its economy.